FACTOR ANALYSIS TO GUEST SATISFACTION DIFFERENTIATED BY INCOME SEGMENT - Rudy Aryanto (Journal of Management and Business, 2011)
Currently fast growing researches on the factors of customer satisfaction, especially in the services sector and tourism. Indonesian as a famous tourism market is going through a period of great change in the current era in term of the demand for tourism destination attraction. One of the tourism destination is Ragunan Zoo Park. To get more market, management should be more pay attention to visitor by increasing in visitor’s satisfaction so that they become a loyal visitors and they will bring more customers to visit Ragunan. The Ragunan’s visitors income can divide in two segment: first, The visitors that have income more regional salary rate (UMR), second, The visitors that have income under regional salary rate. The objectives in this research are: to know are there any variables that differentiation visitor’s satisfaction. Variables that being used base on the customers satisfaction dimension and overall destination product. Data processing and analyzing use Discriminant Analysis. This method was hoped could answer the research objectives. Over all, The research shows any significant differentiation between two groups. Variables that make different are: games ticket, food and beverages price, education image, access, parking facility and count of animals.